The relationship between strength characteristics and performance of elite female Malaysian badminton players across an international season - Webber, G.; Hall, S. (Journal of Australian Strength and Conditioning, 2018)
Lower body strength, frequency of strength training and selective tournament participation are positively related to badminton performance and Badminton World Federation rankings.